Biomass and sugar production dynamics in sweet sorghum variety Roger - López Sandin, Iosvany; Gutiérrez Soto, Guadalupe; Gutiérrez Díez, Adriana; Medina Herrera, Nancy; Gutiérrez Castorena, Edgar; Galicia Juárez, Marisol; Zavala García, Francisco (Instituto de investigaciones agropecuarias, Ministerio de agricultura, 2021)
Sweet sorghum (Sorghum bicolor [L.] Moench) is a crop that is well known for its high production of biomass and sugars in the stem juice. The objective of this work was to evaluate the productivity of sweet sorghum ‘Roger’ based on the dynamics of sugar production and dry biomass by considering different production methods and plant phenological stages. The experimental design consisted of different tillage and fertilization methods established in a randomized complete block design with a split plot arrangement. Tillage treatments were assigned to the plot using the three levels of minimum tillage, traditional tillage, and traditional tillage that included a subsoil operation. Fertilization treatments were assigned to the subplot using the three levels of organic fertilizer, inorganic fertilizer, and without fertilizer. Data collection was performed at different plant phenological stages from anthesis to physiological maturity. Results showed that evaluated agronomic parameters depended on the phenological stage (P < 0.05) rather than the production methods (P > 0.05). Thus, the distribution and accumulation of sugar by stem internodes was associated with plant phenological components. The highest values of the concentration of total soluble solids (14.89%), juice sugar content (22.91 g), juicesugar concentration (527.46 mg g-1 DW), dry biomass (60.04%), and dry biomass yield (19.01 t ha-1) were observed at thephysiological maturity stage of the plant.